2021
DOI: 10.1108/jmtm-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Sociotechnical factors and Industry 4.0: an integrative perspective for the adoption of smart manufacturing technologies

Abstract: PurposeAs the level of implementation of Industry 4.0 increases, misalignments between adopted technologies and organizational factors may result in benefits below expected. This paper aims to analyze how organizational factors can contribute to a higher level of adoption of Industry 4.0 technologies. The paper uses a sociotechnical perspective lens to achieve this aim.Design/methodology/approachUsing a sample of 231 manufacturing companies in Denmark, a leading country in Industry 4.0 readiness, the paper ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
71
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 68 publications
7
71
3
Order By: Relevance
“…However, they stressed that a technocentric adoption approach toward I4.0 does not improve operational performance. Instead, it is a people-centric change of mindset, behavior, and work practices that constitutes a genuinely lean organization, representing the enabling influence of I4.0 (Cagliano et al, 2019;Marcon et al, 2021). A lean organization is characterized by the presence of an organizational learning-to-learn capability (Powell and Coughlan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, they stressed that a technocentric adoption approach toward I4.0 does not improve operational performance. Instead, it is a people-centric change of mindset, behavior, and work practices that constitutes a genuinely lean organization, representing the enabling influence of I4.0 (Cagliano et al, 2019;Marcon et al, 2021). A lean organization is characterized by the presence of an organizational learning-to-learn capability (Powell and Coughlan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, in the literature, we find a multitude of papers encouraging future research to be combined with professionals in the workplace to implement improvement processes such as LM techniques in order to analyse their effect on workers (e.g. Chowdary and George, 2012;Hasle, 2014;Marcon et al, 2021). This recommendation is due to the gap of evidence in this area, as LM papers generally focus on technical improvements in production and do not address workers' perceptions of them.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, in the literature, we find a multitude of papers encouraging future research to be combined with professionals in the workplace to implement improvement processes such as LM techniques in order to analyse their effect on workers (e.g. Chowdary and George, 2012; Hasle, 2014; Marcon et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the current ideas about modern production has found its reflection in the concept of Smart Manufacturing (SM). SM is a production concept that implements computer integration, and a high level of adaptability and a rapid change in production levels, which depends on the demand and the required tasks to solve [ 2 ]. Moreover, [ 2 ] showed that for the usage of digital information techniques that can be implemented for more flexible multiscale dynamic production systems, a single end-to-end industrial network based on IIoT is required.…”
Section: Introductionmentioning
confidence: 99%
“…SM is a production concept that implements computer integration, and a high level of adaptability and a rapid change in production levels, which depends on the demand and the required tasks to solve [ 2 ]. Moreover, [ 2 ] showed that for the usage of digital information techniques that can be implemented for more flexible multiscale dynamic production systems, a single end-to-end industrial network based on IIoT is required. Indeed, the single end-to-end industrial network provides the access to the global Internet network, which supports the connection to all information control actions, besides the interaction with all constituent elements of the SM.…”
Section: Introductionmentioning
confidence: 99%